1992
DOI: 10.1108/19355181199200007
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Coupons: A Double‐Barreled Sales Promotion Technique

Abstract: The use of coupons as a sales promotion technique is not new; manufacturers have been offering cents‐off coupons to customers for over a century. Now, electronic coupons may become the leading edge of a new wave of sales promotion techniques for the 1990s. How much of an impact that wave will make when it hits the American marketplace can only be estimated,but it may indeed be very big.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2116
2116

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The effect of Internet technology on electronic sales factors, such as online advertisement and market research has a significant direct effect on businesses' market growth. This is consistent with previous studies which shown a positive impact of Internet marketing activities on electronic sales [9].…”
Section: E-salessupporting
confidence: 93%
See 2 more Smart Citations
“…The effect of Internet technology on electronic sales factors, such as online advertisement and market research has a significant direct effect on businesses' market growth. This is consistent with previous studies which shown a positive impact of Internet marketing activities on electronic sales [9].…”
Section: E-salessupporting
confidence: 93%
“…Through the begging of time man human kind were constantly seeking new ways to improve their ways of living and that is the reason of Technology invention which evolved in many ways and sectors [9]. Nowadays Technology has many derivatives.…”
Section: E-procurement and Technology Monitoring As Marketing And Socmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of using e-coupons by travel agencies match the benefits of using e-coupons in the retail business generally. This includes driving business, generating new users and increasing overall user spending as a result of attracting new customers and encouraging repurchase behavior in existing customers (Hoffman, Ketcham & Taylor III, 1992;McKenzie & Tullock, 2012;Business News Daily, 2011;Common Kindness, 2012). Besides, e-coupons are the most likely to influence consumer purchase decisions (Hoffman, et al, 1992;Chiou-Wei & Inman, 2008).…”
Section: The Advantages and Concerns Of Using E-coupons By Travel Com...mentioning
confidence: 99%
“…This includes driving business, generating new users and increasing overall user spending as a result of attracting new customers and encouraging repurchase behavior in existing customers (Hoffman, Ketcham & Taylor III, 1992;McKenzie & Tullock, 2012;Business News Daily, 2011;Common Kindness, 2012). Besides, e-coupons are the most likely to influence consumer purchase decisions (Hoffman, et al, 1992;Chiou-Wei & Inman, 2008). Studies show that 88% of visitors to coupon websites agreed that e-coupons close the deal for them when they are undecided on a purchase and 47% of consumers would try a new product when receiving an e-coupon (Forrester Consulting, 2014, p.5).…”
Section: The Advantages and Concerns Of Using E-coupons By Travel Com...mentioning
confidence: 99%